A 20-Minute Decision-delivery Interval at Emergency Cesarean Section Using General Anesthesia: A Clinically Relevant Target. Issue 2 (24th June 2022) - Kinsella, S.M.
Abstract : ( Anaesthesia . 2021;76:1021–1025) The 30-minute decision-delivery interval for emergency cesarean is deeply embedded as a standard of quality of care in such cases in Europe and the United States. In extreme circumstances a shorter decision-delivery time of 20 minutes is supported where placental function or fetal circulation are severely and irreversibly compromised.